(untitled) (Security Dialogues, 2023)
An important functioning aspect of the prison community is its social climate, composed by the interdependencies of the subdimensions such as: deprivation, the prisoncode (informal aspect of the prison), repression and disorganization (the formal aspect ofimprisonment) that defines the direction and movement of this community through a complexenvironment in an effort to explain or use that for its own purpose. The social climate wasmeasured by a custom inventory of attitudes originally created by R.H. Moos in a closed-typeprison in Zenica, Bosnia and Herzegovina. In this paper, we focus on a prison code based onvalues that the prisoners have in the time-space of the prison. The prison code is a theoreticalconstruct that has its reality in prison experience. In this work, we present the correlation andmultiple values of the prison code in relation to other subdimensions of the social climatefrom 1991, 1993, 1994, 1997 and 2016. In all samples more than 80% of prisoners wereincluded, except for 2016 were approximately 20% of prisoners were included in the sample.All the individual and multiple correlations of the prison code with other subdimensions arestatistically significant (I will specifically present them during the presentation) and it seemst hat has a significant impact on a scenario that takes place in prison; ranging from a riot, to its normal day-to-day functioning.